Metabody in Posthuman Architecture: Virtualizing Spatial Dynamics for Transformative Spaces - Kuran, İpek (Journal of Posthumanism, 2023)
This research examines the concepts of metahumanism and metabody to explore the production of posthuman space. It examines the dynamic nature of posthuman space, which is characterized by fluidity, lack of form, and the interplay of relationships and interactions. Using Deleuze’s distinction between the virtual and the actual, this study examines how posthuman space emerges as a convergence of these concepts, continuously shifting between fluid and solid states to accommodate the diverse posthuman experience. Virtualization is a crucial instrument for investigating posthuman architecture, especially within digital environments that foster creative expression and experimentation. Through a case study, this research examines the role of virtualization in forming a posthuman architectural landscape, demonstrating how digital domains offer unique opportunities for innovative space production and exploration. By highlighting the novel spaces that can be realized through virtualization, the study demonstrates the ability of posthuman architecture to cultivate new modes of interaction and engagement, thereby fundamentally altering our relationship with and perception of the built environment. This research contributes to the comprehension of the influence of virtualization on the formation of a posthuman architectural landscape by shedding light on its transformative capacities and implications.